Comparison of the anti-adhesive effect of clarithromycin and tetracycline - Simsek, M.; Atilgan, R.; Ozkan, Z. S.; Kavak, B.; Deveci, D.; Demirel, I.; Sapmaz, E. (Oxford Univ Press, 2013)
[Abstract Not Available]
29th Annual Meeting of the European-Society-of-Human-Reproduction-and-Embryology (ESHRE) -- JUL 07-10, 2013 -- London, ENGLAND